Zinc Finger Transcription Factor Zbtb16 Coordinates the Response to Energy Deficit in the Mouse Hypothalamus - Cheng, Helia; Pablico, Schuyler J.; Lee, Jisu; Chang, Ji Suk; Yu, Sangho (Frontiers in Neuroscience, 2020)
The central nervous system controls feeding behavior and energy expenditure in response to various internal and external stimuli to maintain energy balance. Here we report that the newly identified transcription factor zinc finger and BTB domain containing 16 (Zbtb16) is induced by energy deficit in the paraventricular (PVH) and arcuate (ARC) nuclei of the hypothalamus via glucocorticoid (GC) signaling. In the PVH, Zbtb16 is expressed in the anterior half of the PVH and co-expressed with many neuronal markers such as corticotropin-releasing hormone (Crh), thyrotropin-releasing hormone (Trh), oxytocin (Oxt), arginine vasopressin (Avp), and nitric oxide synthase 1 (Nos1). Knockdown (KD) of Zbtb16 in the PVH results in attenuated cold-induced thermogenesis and improved glucose tolerance without affecting food intake. In the meantime, Zbtb16 is predominantly expressed in agouti-related neuropeptide/neuropeptide Y (Agrp/Npy) neurons in the ARC and its KD in the ARC leads to reduced food intake. We further reveal that chemogenetic stimulation of PVH Zbtb16 neurons increases energy expenditure while that of ARC Zbtb16 neurons increases food intake. Taken together, we conclude that Zbtb16 is an important mediator that coordinates responses to energy deficit downstream of GCs by contributing to glycemic control through the PVH and feeding behavior regulation through the ARC, and additionally reveal its function in controlling energy expenditure during cold-evoked thermogenesis via the PVH. As a result, we hypothesize that Zbtb16 may be involved in promoting weight regain after weight loss.